Pengaruh Personality Traits dan Literasi Keuangan terhadap Intensi Berwirausaha Mahasiswa - Nesi - Hasanah; Friyatmi Friyatmi (Jurnal Ecogen, 2023)
This research aims to analyze the effect of 1) Personality Traits on Financial Literacy of Economic Education Students 2) Personality Traits on Entrepreneurial Intentions of  Economic Education Students 3) Financial Literacy on Entrepreneurial Intentions of Economics Education Students. This is a  quantitative research with a causative approach. The  technique of sampling is proportional random sampling and the number of  sample is  85 students economic education . The data used are secondary and primary data. The data was collected using documentation and questionnaires. It analyzed using path analysis, t test and coefficient of determination with SPSS aplication and alpha 0.05. The results shown that 1) Personality Traits has a impact in  poitive on Financial Literacy but it is insignificant  2) Personality Traits has a positive impact and significant on Entrepreneurial Intentions 3) Financial Literacy has a negative and insignificant on intentions of  entrepreneurial.